COVID-19: Hygiene and Public Health to the front - Signorelli, Carlo; Fara, Gaetano Maria (Acta Biomedica Atenei Parmensis, 2020)
Public Health professionals and academics have been on the frontline of Italian history during the COVID-19 response like they never did before. Ancient professors of Hygiene such as Celli, Pagliani, Sclavo, Petragnani, Seppilli and Giovanardi flanked politicians in other critical moments. They helped them to manage healthcare reforms, earthquakes response, Seveso Dioxin disaster, cholera and poliomielitis epidemics and other health threats. The ongoing COVID-19 epidemic has highlighted the paramount importance of the practical application of basic concepts of public health, which were considered so far became obsolete, such as personal hygiene, quarantine, individual protective devices or basic epidemiological measures. Hygiene and Public Health used to have a targeted audience in professionals and lecturers. Nowadays, these topics are critical and of concern of a much larger audience. Public Health women and men are now asked to act in task forces, media broadcasts, webinars and consulting activities. In phase 2 of this epidemic - which is about to begin when this volume is to be published – the role of Public Health professionals could become even more relevant. However, this unexpected season must be managed with seriousness and intelligence, capitalizing it also for the future. If our Post-Graduate Schools of Public Health ("Igiene e Medicina Preventiva"), our scientific associations, our academic lecturers and our officers do not prove to be up to the situation, a dull future for the discipline might very well be. On the contrary, if as we all hope, we will be able to ride the wave of a dramatic health crisis, transforming it into a relevant scientific and professional opportunity, then we will be able to build on the post-COVID-19 a cutting-edge, a more attractive, relevant and modern discipline. This Supplement of Acta Biomedica, planned before the onset of the epidemic emergency in Italy, but already successful in presenting two papers on COVID-19, is further proof of how current and lively our discipline is.